2021
DOI: 10.1016/j.jbc.2021.100446
|View full text |Cite
|
Sign up to set email alerts
|

Loss of bound zinc facilitates amyloid fibril formation of leukocyte-cell-derived chemotaxin 2 (LECT2)

Abstract: Aggregation of the circulating protein leukocyte-cell-derived chemotaxin 2 (LECT2) causes amyloidosis of LECT2 (ALECT2), one of the most prevalent forms of systemic amyloidosis affecting the kidney and liver. The I40V mutation is thought to be necessary but not sufficient for ALECT2, with a second, as-yet undetermined condition being required for the disease. EM, X-ray diffraction, NMR, and fluorescence experiments demonstrate that LECT2 forms amyloid fibrils in vitro in the absence of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 41 publications
1
28
3
Order By: Relevance
“…However, in our study, we found obvious amyloid deposits in the interstitium of renal medulla in Patient 1, which were positive for LECT2 in IHC. Genetic analysis of this patient revealed a single base transversion from A to G at position 172 of the LECT2 gene [c.172A>G (p.Ile58Val; NM_002302)], this is a common polymorphism (SNP rs31517) that are thought to be present in all ALECT2 amyloidosis patients ( 16 ). These evidences support that this patient coexisted with ALECT2 amyloidosis.…”
Section: Discussionmentioning
confidence: 94%
“…However, in our study, we found obvious amyloid deposits in the interstitium of renal medulla in Patient 1, which were positive for LECT2 in IHC. Genetic analysis of this patient revealed a single base transversion from A to G at position 172 of the LECT2 gene [c.172A>G (p.Ile58Val; NM_002302)], this is a common polymorphism (SNP rs31517) that are thought to be present in all ALECT2 amyloidosis patients ( 16 ). These evidences support that this patient coexisted with ALECT2 amyloidosis.…”
Section: Discussionmentioning
confidence: 94%
“…Although regulation of Angpl8 by insulin has been reported [50], free hINS had no impact on either Clec2d or Angpl8 in our study. In contrast, Ca 2+ -dependent actin-binding plastin 1 (Pls1) [51] and amyloidogenic leukocyte-cell-derived chemotaxin 2 [52] (Lect2) were upregulated by free AAC2 and suppressed by the AAC2-hINS complex. Free hINS did not influence these genes.…”
Section: Aac2-hins Improved Cognitive Performance In T1d Mouse Modelsmentioning
confidence: 99%
“…Each sensor construct was eluted as a monomeric species from a Superdex S200 Increase size exclusion column (Cytiva) and was judged to be > 95% pure by SDS-PAGE (Figure S5). The circularly permuted FKBP gene was inserted into the Thermoanaerobacter tengcongensis ribose binding protein gene as described by Ha et al 33 The cpFKBP-RBP fusion protein was expressed and purified as described above, after which RBP was cleaved off using HRV-3C protease. Free cpFKBP was recovered by passing the digested solution through a nickel-nitriloacetic acid column to remove free RBP and undigested cpFKBP-RBP.…”
Section: Gene Construction and Protein Purificationmentioning
confidence: 99%